Penghitungan Nilai Karbon Pada Kawasan Hutan Di Provinsi Bali - I GUSTI RAKAWISNU; I PUTU GEDE ARDHANA; GEDE WIJANA (Fakultas Pertanian Universitas Udayana, 2013)
Calculated Carbon Values of The Forest in Bali Province In its position as a life support system, the forest has been of great benefit to humankind, therefore, should be preserved. in its position as a life support system. Current issues that has not been the effort to determine the carbon content of vegetation contained in the forest in Bali Province so is not known how important the existence of the forest. This study is intended to complete the task and provide a general description of the importance of forests as a buffer of life. Implementation of forest carbon values ??calculated using the data of the activities Permanent Sample Plots (PSP) in Bali Province processed to obtain the amount of biomass and amount of carbon. Composition of the stands in each plot by arranging the order of INV species of minimum value to maximum INV the maximum in each plot ranged from 39.79% to 165.31% . forest stand structure in order of number of poles minimum value to a maximum of 35 rods ranging up to 249 while the number of tree trunks as much as 39 to 178 rods. the average diameter of stands in each plot ranged from 11.24 cm to 36.65 cm . forest stand structure in each plot based on high order of maximum to minimum values ??ranging from 2 m to 5 m , while the maximum height ranges from 8 m to 26 m . average height standing of tree in each plot ranged from 4.85 m to 10.48 m. forest stand volume ranged from 104.93 t C/ha to 287.38 t C/ha with an average value of carbon 168.72 t C/ha. The entire plot is in the province of Bali is dominated by stands of the carbon value of class 60-80 t C/ha with a total area of ??6 ha plot, followed by the class standing of the carbon value of 100-200 t C/ha and 80-100t C/ha, with the total area of ??the plot in a row 3 and 2 ha, as well as by class standing of the carbon value <60 t C/ha and> 120 t C/ha, with a total area of each plot of 1 ha.